Solid waste fluorogypsum activator for mine filling and preparation method and application thereof
By preparing activators from fluorogypsum, industrial waste residue, and sodium sulfate, the dehydration problem caused by excessively high cement temperatures was solved, the fluidity and strength of the backfill material were improved, the backfill cost was reduced, and excellent dustproof and moisture-retaining properties were provided in mining environments.
Patent Information
- Application Number
- CN202511214358.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-08-28
AI Technical Summary
In existing technologies, excessively high cement temperatures can cause desulfurized gypsum to dehydrate, leading to cement clumping, which affects the cement's fluidity and increases the difficulty of filling material construction.
Fluorogypsum, industrial waste residue, and sodium sulfate were ground and activated together. A composite early-strength agent made from coagulation-promoting adsorption particles, triethanolamine, and calcium formate was added and mixed with ethylene glycol to prepare a solid waste fluorogypsum activator for mine backfilling. This agent promotes hydration reaction, replaces part of the cement, and reduces carbon emissions.
It improves the strength and fluidity of the filling material, saves gelation time, reduces filling costs, meets the needs of mine filling materials, and provides excellent dust prevention and moisture retention performance in open-air environments through environmentally friendly dust suppressants.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of mine backfill activator manufacturing technology, specifically relating to solid waste fluorogypsum activator for mine backfilling, its preparation method and application. Background Technology
[0002] Current industry standards for underground mining of both metallic and non-metallic materials require that all underground mines employ backfilling methods to reduce ground pressure disasters caused by goafs. For mine backfill materials, the requirements for deformation shrinkage and long-term strength are not high, but the requirements for stability, durability, and corrosion resistance are relatively high. In traditional backfill materials, cement is the main cost component, accounting for over 50%. This high cost hinders the development and widespread application of backfill mining. Therefore, to reduce cemented backfill costs without compromising the strength of the backfill material, using low-cost solid waste to replace cement is an important research direction in the field of backfill materials.
[0003] Fluoropyrogypsum, a byproduct of hydrofluoric acid production using sulfuric acid and fluorite, is primarily composed of type II calcium sulfate. Its main phase composition is similar to that of natural anhydrite, and it possesses potential hydration activity. A large amount of fluorogypsum waste is generated annually, but its current applications are limited, mainly in the construction industry. Therefore, most fluorogypsum is simply stockpiled, and residual acid in it can seep into the surrounding environment and pollute it through rainwater runoff. Thus, it is necessary to explore ways to broaden the utilization of fluorogypsum. When used as a mine backfill material, fluorogypsum suffers from insufficient hydration rate to form dihydrate gypsum. It is necessary to activate fluorogypsum through grinding or the addition of activators to improve its hydration properties and meet the requirements of mine backfill materials.
[0004] Chinese invention patent CN113060961B discloses an activator for mine backfill materials and its preparation method. The activator comprises 76-78 parts steel slag, 14-16 parts sodium silicate, 2-4 parts aluminum sulfate, and 4-6 parts ammonium sulfate. It also includes a superabsorbent polymer, calcium oxide, and alkali-treated microcrystalline cellulose. The preparation method includes steps such as crushing materials, mixing powdered steel slag and powdered sodium silicate, adding powdered aluminum sulfate, and adding powdered ammonium sulfate. The method further includes steps such as adding superabsorbent polymer, adding calcium oxide, and adding alkali-treated microcrystalline cellulose. The activator obtained using this invention can improve the product qualification rate of the cementitious agent, reduce production costs, give the activator better fluidity, and provide stronger alkalinity, resulting in good economic and social benefits. However, existing technologies have a technical problem: when the cement temperature is too high, desulfurized gypsum will dehydrate, causing the cement to clump and affecting its fluidity. Summary of the Invention
[0005] The purpose of this invention is to provide a solid waste fluorogypsum activator for mine backfilling, its preparation method and application, to solve the technical problem in the prior art that desulfurized gypsum dehydrates when the cement temperature is too high, causing the cement to clump and affecting the fluidity of the cement.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] The solid waste fluorogypsum activator for mine backfilling is prepared from the following components in parts by weight:
[0008] 80-90 parts of fluorogypsum, 10-15 parts of industrial waste residue, 0.1-0.3 parts of composite early strength agent, 2-5 parts of sodium sulfate, and 0.01-0.03 parts of ethylene glycol;
[0009] The fluorogypsum is a byproduct of hydrofluoric acid production, the industrial waste residue is one or both of blast furnace slag and fly ash, and the mirabilite is a byproduct of soda ash production.
[0010] The preparation method of the composite early strength agent includes the following steps:
[0011] S11. Add calcium chloride and aluminum chloride to an ethanol aqueous solution, add sodium carbonate and sodium hydroxide in an ethanol aqueous solution to control the pH, raise the temperature to crystallize the reaction, filter to collect the solid, and dry to obtain calcium aluminum hydrotalcite.
[0012] S12. Acrylic acid, vinyl polyethylene glycol ether, 2-acrylamido-2-methylpropanesulfonic acid and calcium aluminum hydrotalcite are added to a reaction vessel, deionized water is added and stirred to disperse, sodium sulfite and ammonium persulfate are added dropwise to the reaction vessel, the temperature is raised to react and polymerize, the solid is collected by filtration, washed with ethanol, and dried to obtain coagulation adsorption particles.
[0013] S13. Mix and grind the coagulation-promoting adsorption particles, triethanolamine and calcium formate to obtain a composite early strength agent.
[0014] Preferably, in S11, the molar ratio of calcium chloride to aluminum chloride is 2-3, the ethanol aqueous solution is prepared by mixing ethanol and deionized water at a volume ratio of 1:1, the molar ratio of sodium carbonate to sodium hydroxide in the ethanol aqueous solution of sodium carbonate and sodium hydroxide is 1:4, the pH is controlled at 9-10, the temperature is raised to 80-90℃ for crystallization reaction for 10-12 hours, and then dried at 60-70℃.
[0015] Preferably, the ratio of acrylic acid, vinyl polyethylene glycol ether, 2-acrylamido-2-methylpropanesulfonic acid, calcium aluminum hydrotalcite, deionized water, sodium sulfite, and ammonium persulfate in S12 is (50~55) g : (25~30) g : (5~5.5) g : (3.5~5.5) g : (200~300) mL : (0.8~1.2) g : (1.5~2) g. The mixture is stirred and dispersed at a speed of 70~150 rpm. The sodium sulfite and ammonium persulfate are added dropwise over a period of 1~1.5 h. The mixture is heated to 60~70 °C and reacted for 3~6 h. The mixture is then dried at 60~70 °C.
[0016] Preferably, the mass ratio of the coagulation-promoting adsorption particles, triethanolamine, and calcium formate in S13 is 2~4:5~8:1.25~2.
[0017] The preparation method of the solid waste fluorogypsum activator for mine backfilling includes the following steps:
[0018] S1. Fluorogypsum, industrial waste residue and sodium sulfate are added to a grinding mill, ground and sieved to obtain an activator for later use;
[0019] S2. Add the activator and composite early strength agent to the mixer, add ethylene glycol dropwise, and stir to prepare the solid waste fluorogypsum activator for mine backfilling.
[0020] Preferably, in step S1, the grinding and sieving to 200 mesh has a pass rate of over 70%.
[0021] Preferably, in step S2, the mixer is stirred and mixed at a speed of 70-150 rpm for 10-15 minutes.
[0022] The application of solid waste fluorogypsum activator for mine backfilling, used in mine backfill materials, includes the following steps:
[0023] S21. Solid waste fluorogypsum activator, slag powder and cement used for mine backfilling are added to a mixer and mixed to obtain cement powder. Industrial water and tailings are added and stirred to obtain slurry.
[0024] S22. The grout is injected into the unfilled mining area. After solidification, an environmentally friendly dust suppressant is added to industrial water and sprayed in a mist form using a high-pressure water mist method to cure and obtain the mine filling material.
[0025] Preferably, in S21, the mass ratio of solid waste fluorogypsum activator, slag powder and cement is 20~30:60~70:10~15, the water-solid ratio of slurry is 0.6~0.7, and the mass ratio of cementitious powder and whole tailings is 1:4~10.
[0026] Preferably, the amount of environmentally friendly dust suppressant added in step S22 is 5-8% of the mass of industrial water, and the unit spraying rate is 0.6-0.9 L / m³.2 1-3 days of maintenance.
[0027] Preferably, the method for preparing the environmentally friendly dust suppressant in S22 includes the following steps:
[0028] S31. Soybean oil and glyceryl monolaurate are added to a reaction vessel, heated and stirred to form an oil phase. Esterified starch and carboxymethyl cellulose are added to deionized water, heated and stirred until completely gelatinized, and then the oil phase is added. The emulsion is prepared by high-speed shearing and stirring, and a biodegradable wetting agent is obtained by spray drying.
[0029] S32. A biodegradable wetting agent, polyethylene glycol and sodium lignosulfonate are mixed to prepare an environmentally friendly dust suppressant.
[0030] Preferably, in S31, the mass ratio of soybean oil to glyceryl monolaurate is 100:4~5, and the mixture is heated to 50~60℃ and stirred to form an oil phase. The mass ratio of the oil phase, esterified starch, carboxymethyl cellulose and deionized water is 3~5:10~20:2~5:100.
[0031] Preferably, in step S31, the temperature is raised to 80-90℃ and stirred at 200-300 rpm for 1-2 hours until complete gelatinization. After adding the oil phase, the mixture is sheared and stirred at 3000-4000 rpm for 1-3 minutes. The spray drying parameters are: inlet air temperature of 160-180℃, outlet air temperature of 60-80℃, and air volume of 500-800 m³ / h. 3 / h, wind speed is 0.8~1.5 m / s.
[0032] Preferably, the mass ratio of the biodegradable wetting agent, polyethylene glycol, and sodium lignosulfonate in S32 is 2~2.5:0.8~1:0.1~0.2.
[0033] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0034] 1. This invention relates to a solid waste fluorogypsum activator for mine backfilling, prepared by co-grinding and activating fluorogypsum, industrial waste residue, and sodium sulfate, and then mixing them with a composite early-strength agent made from coagulation-promoting adsorption particles, triethanolamine, and calcium formate, and ethylene glycol. The composite early-strength agent is made from coagulation-promoting adsorption particles, triethanolamine, and calcium formate. The coagulation-promoting adsorption particles are made by cross-coating calcium aluminum hydrotalcite with acrylic acid, vinyl polyethylene glycol ether, and 2-acrylamido-2-methylpropanesulfonic acid. The solid waste fluorogypsum activator for mine backfilling of this invention adopts... By grinding and activating various solid wastes together, the crystal structure of fluorogypsum is destroyed, creating lattice defects that facilitate hydration reactions. The vitreous components of industrial waste dissociate, and calcium enters the reaction system, promoting the hydration reaction to generate calcium silicate hydrate, which enhances gelling activity. Furthermore, it neutralizes the alkaline substances remaining in the industrial waste and the acidic substances remaining in the fluorogypsum. It can replace some cement, reduce carbon emissions, and when used in mine backfill materials, it can improve the strength of the backfill, save gelling time, and increase mine production efficiency.
[0035] 2. The coagulation-promoting adsorption particles prepared by cross-coating calcium aluminum hydrotalcite with acrylic acid, vinyl polyethylene glycol ether, and 2-acrylamido-2-methylpropanesulfonic acid in this invention exhibit excellent coagulation-promoting and impurity-adsorption properties. As a fine filler material, it promotes the early hydration reaction of cement by providing more active sites. The calcium aluminum hydrotalcite has a layered spatial structure, which can adsorb chloride ions and solidify them, alleviating the problem of prolonged gelation time of the filling material caused by impurity penetration. The carboxylic acid groups and sulfonic acid groups can be intercalated on the surface of calcium aluminum hydrotalcite through electrostatic adsorption, improving the dispersibility of the coagulation-promoting adsorption particles. The polyethylene glycol ether groups are hydrophilic, improving the water retention performance of the coagulation-promoting adsorption particles. The composite early-strength agent prepared by the coagulation-promoting adsorption particles, triethanolamine, and calcium formate can form a complex with calcium ions, regulate the ion concentration of cement paste, and promote the growth of hydration products.
[0036] 3. This invention involves gelatinizing esterified starch and carboxymethyl cellulose in deionized water, then adding soybean oil and glyceryl monolaurate to prepare an oil phase. The oil phase is then subjected to high-speed shearing and stirring to prepare an emulsion. A biodegradable wetting agent is obtained through spray drying. Polyethylene glycol and sodium lignosulfonate are then added to prepare an environmentally friendly dust suppressant. This process prevents excessive use of sodium lignosulfonate from corroding instruments. The esterified starch and carboxymethyl cellulose coat the oil phase to form a porous membrane. The biodegradable wetting agent adsorbs dust and reduces moisture evaporation, making it difficult for droplets to disperse in strong winds. It directly impacts and encapsulates dust particles, providing windproof performance. The environmentally friendly dust suppressant prepared by this invention exhibits excellent dustproof and moisturizing properties in open-pit mining environments. Detailed Implementation
[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] The fluorogypsum involved in this invention is a byproduct of the production of hydrofluoric acid, and the mass percentages of each component are as follows: silicon dioxide 0.93%, aluminum oxide 0.67%, calcium oxide 44.31%, magnesium oxide 0.16%, sulfur trioxide 52.42%, and other impurities 1.51%.
[0039] The mass percentages of each component in blast furnace slag are as follows: silicon dioxide 37.23%, aluminum oxide 11.68%, calcium oxide 39.68%, magnesium oxide 6.24%, iron oxide 0.57%, and other impurities 4.6%.
[0040] The fly ash is grade I fly ash, and the mass percentage of each component is as follows: silicon dioxide 45.96%, aluminum oxide 15.23%, calcium oxide 26.98%, magnesium oxide 0.96%, iron oxide 6.52%, alkaline salts 0.31%, and other impurities 4.04%.
[0041] The slag powder is S95 grade slag powder produced in accordance with GB / T 18046-2017 "Granulated blast furnace slag powder for use in cement and concrete".
[0042] Example 1: The solid waste fluorogypsum activator for mine backfilling in this example is prepared from the following components:
[0043] 80 kg of fluorogypsum, 15 kg of blast furnace slag, 220 g of composite early strength agent, 3 kg of sodium sulfate and 10 g of ethylene glycol.
[0044] The preparation method of the composite early strength agent in this embodiment includes the following steps:
[0045] S11. Prepare an ethanol-water solution by mixing ethanol and deionized water at a volume ratio of 1:1. Add 17g of calcium chloride and 10g of aluminum chloride to 200mL of the ethanol-water solution. Add dropwise 8g of sodium carbonate and 12g of sodium hydroxide dissolved in 100mL of ethanol-water solution to control the pH to 9.5. Raise the temperature to 80℃ and crystallize for 12h. Filter and collect the solid. Dry at 60℃ to obtain calcium aluminum hydrotalcite.
[0046] S12. Add 55g of acrylic acid, 30g of vinyl polyethylene glycol ether, 5.5g of 2-acrylamido-2-methylpropanesulfonic acid and 5g of calcium aluminum hydrotalcite to a reaction vessel, add 300mL of deionized water and disperse at 100rpm, add 1.2g of sodium sulfite and 2g of ammonium persulfate dropwise to the reaction vessel over a period of 1.5h, heat to 70℃ and react for 3h, filter to collect the solid, wash with ethanol, and dry at 60℃ to obtain coagulation adsorption particles.
[0047] S13. Mix and grind 60g of coagulation-promoting adsorption particles, 120g of triethanolamine and 30g of calcium formate to prepare a composite early strength agent.
[0048] The preparation method of the solid waste fluorogypsum activator for mine backfilling in this embodiment includes the following steps:
[0049] S1. Add fluorogypsum, blast furnace slag and sodium sulfate to a grinding mill, grind and sieve to 200 mesh with a passing rate of over 70%, to obtain an activator for later use;
[0050] S2. Add the activator and composite early strength agent to the mixer, add ethylene glycol dropwise, and mix at 150 rpm for 10 minutes to obtain the solid waste fluorogypsum activator for mine backfilling.
[0051] The application of the solid waste fluorogypsum activator for mine backfilling in this embodiment, used in mine backfilling materials, includes the following steps:
[0052] S21. Add 20kg of solid waste fluorogypsum activator for mine backfilling, 70kg of slag powder and 10kg of cement to a mixer and mix to obtain cementitious powder. Add industrial water and tailings and stir to obtain slurry. The water-solid ratio of the slurry is 0.6 and the mass ratio of cementitious powder to tailings is 1:4.
[0053] S22. The grout is injected and filled into the unused mining area. After solidification, an environmentally friendly dust suppressant is added to the industrial water and sprayed as a mist using a high-pressure water spray method. The amount of environmentally friendly dust suppressant added is 5% of the mass of the industrial water, and the unit spraying rate is 0.6 L / m³. 2 The mine filling material was prepared by curing for 1 day.
[0054] The method for preparing the environmentally friendly dust suppressant in this embodiment includes the following steps:
[0055] S31. Add 2.5 kg of soybean oil and 0.1 kg of glyceryl monolaurate to a reaction vessel, heat to 60°C and stir to form an oil phase. Add 5 kg of esterified starch and 1 kg of carboxymethyl cellulose to 50 kg of deionized water, heat to 80°C and stir at 200 rpm for 2 hours until completely gelatinized. Then add 2 kg of the oil phase and shear and stir at 3000 rpm for 3 minutes to prepare an emulsion. Obtain a biodegradable wetting agent by spray drying. The spray drying parameters are: inlet air temperature of 180°C, outlet air temperature of 80°C, and air volume of 500 m³ / h. 3 / h, wind speed is 0.8 m / s.
[0056] S32. Mix 2.5 kg of biodegradable wetting agent, 1 kg of polyethylene glycol and 0.2 kg of sodium lignosulfonate to prepare an environmentally friendly dust suppressant.
[0057] Example 2: The solid waste fluorogypsum activator for mine backfilling in this example is prepared from the following components:
[0058] 85 kg of fluorogypsum, 10 kg of fly ash, 100 g of composite early strength agent, 4 kg of sodium sulfate and 20 g of ethylene glycol.
[0059] The preparation method of the composite early strength agent in this embodiment includes the following steps:
[0060] S11. Prepare an ethanol-water solution by mixing ethanol and deionized water at a volume ratio of 1:1. Add 20g of calcium chloride and 11g of aluminum chloride to 250mL of the ethanol-water solution. Add dropwise 8g of sodium carbonate and 12g of sodium hydroxide dissolved in 100mL of ethanol-water solution to control the pH at 10. Heat to 90℃ and crystallize for 10h. Filter to collect the solid and dry at 65℃ to obtain calcium aluminum hydrotalcite.
[0061] S12. Add 50g of acrylic acid, 25g of vinyl polyethylene glycol ether, 5g of 2-acrylamido-2-methylpropanesulfonic acid and 3.5g of calcium aluminum hydrotalcite to a reaction vessel, add 200mL of deionized water and disperse at 70rpm, add 0.8g of sodium sulfite and 1.6g of ammonium persulfate dropwise to the reaction vessel over 1h, heat to 60℃ and react for 4h, filter to collect the solid, wash with ethanol, and dry at 60℃ to obtain coagulation adsorption particles;
[0062] S13. Mix and grind 20g of coagulation-promoting adsorption particles, 65g of triethanolamine and 15g of calcium formate to prepare a composite early strength agent.
[0063] The preparation method of the solid waste fluorogypsum activator for mine backfilling in this embodiment includes the following steps:
[0064] S1. Add fluorogypsum, fly ash and sodium sulfate to a grinding mill, grind and sieve to 200 mesh with a passing rate of over 70%, to obtain an activator for later use;
[0065] S2. Add the activator and composite early strength agent to the mixer, add ethylene glycol dropwise, and mix at 70 rpm for 10 minutes to obtain the solid waste fluorogypsum activator for mine backfilling.
[0066] The application of the solid waste fluorogypsum activator for mine backfilling in this embodiment, used in mine backfilling materials, includes the following steps:
[0067] S21. Add 30 kg of solid waste fluorogypsum activator for mine backfilling, 60 kg of slag powder and 10 kg of cement to a mixer and mix to obtain cementitious powder. Add industrial water and tailings and stir to obtain slurry. The water-solid ratio of the slurry is 0.65 and the mass ratio of cementitious powder to tailings is 1:6.
[0068] S22. The grout is injected and filled into the unused mining area. After solidification, an environmentally friendly dust suppressant is added to the industrial water and sprayed as a mist using a high-pressure water spray method. The amount of environmentally friendly dust suppressant added is 5-8% of the mass of the industrial water, and the unit spraying rate is 0.9 L / m³. 2 The mine filling material was prepared by curing for 2 days.
[0069] The method for preparing the environmentally friendly dust suppressant in this embodiment includes the following steps:
[0070] S31. Add 2.5 kg of soybean oil and 0.11 kg of glyceryl monolaurate to a reaction vessel, heat to 60°C and stir to form an oil phase. Add 10 kg of esterified starch and 2.5 kg of carboxymethyl cellulose to 50 kg of deionized water, heat to 90°C and stir at 200 rpm for 2 hours until completely gelatinized. Then add 2.5 kg of the oil phase and shear and stir at 3500 rpm for 3 minutes to prepare an emulsion. Obtain a biodegradable wetting agent by spray drying. The spray drying parameters are: inlet air temperature 160°C, outlet air temperature 60°C, and air volume 700 m³ / h. 3 / h, wind speed is 1.2 m / s.
[0071] S32. Mix 2 kg of biodegradable wetting agent, 1 kg of polyethylene glycol and 0.1 kg of sodium lignosulfonate to prepare an environmentally friendly dust suppressant.
[0072] Example 3: The solid waste fluorogypsum activator for mine backfilling in this example is prepared from the following components:
[0073] 90 kg of fluorogypsum, 10 kg of industrial waste residue, 300 g of composite early strength agent, 5 kg of sodium sulfate and 30 g of ethylene glycol.
[0074] The industrial waste residue is prepared by mixing blast furnace slag and fly ash in a mass ratio of 1:1.
[0075] The preparation method of the composite early strength agent in this embodiment includes the following steps:
[0076] S11. Prepare an ethanol-water solution by mixing ethanol and deionized water at a volume ratio of 1:1. Add 25g of calcium chloride and 12g of aluminum chloride to 300mL of the ethanol-water solution. Add dropwise 8g of sodium carbonate and 12g of sodium hydroxide dissolved in 100mL of ethanol-water solution to control the pH at 10. Heat to 90℃ and crystallize for 12h. Filter to collect the solid and dry at 70℃ to obtain calcium aluminum hydrotalcite.
[0077] S12. Add 50g of acrylic acid, 30g of vinyl polyethylene glycol ether, 5.5g of 2-acrylamido-2-methylpropanesulfonic acid and 5.5g of calcium aluminum hydrotalcite to a reaction vessel, add 300mL of deionized water and disperse at 150rpm, add 1.2g of sodium sulfite and 2g of ammonium persulfate dropwise to the reaction vessel over a period of 1.5h, heat to 70℃ and react for 4h, filter to collect the solid, wash with ethanol, and dry at 60℃ to obtain coagulation adsorption particles;
[0078] S13. Mix and grind 160g of coagulation-promoting adsorption particles, 200g of triethanolamine and 50g of calcium formate to prepare a composite early strength agent.
[0079] The preparation method of the solid waste fluorogypsum activator for mine backfilling in this embodiment includes the following steps:
[0080] S1. Add fluorogypsum, industrial waste residue and sodium sulfate to a grinding mill, grind and sieve to 200 mesh with a passing rate of over 70%, to obtain an activator for later use;
[0081] S2. Add the activator and composite early strength agent to the mixer, add ethylene glycol dropwise, and mix at 150 rpm for 15 minutes to obtain the solid waste fluorogypsum activator for mine backfilling.
[0082] The application of the solid waste fluorogypsum activator for mine backfilling in this embodiment, used in mine backfilling materials, includes the following steps:
[0083] S21. Add 30kg of solid waste fluorogypsum activator for mine backfilling, 70kg of slag powder and 15kg of cement to a mixer and mix to obtain cementitious powder. Add industrial water and tailings and stir to obtain slurry. The water-solid ratio of the slurry is 0.7 and the mass ratio of cementitious powder to tailings is 1:10.
[0084] S22. The grout is injected and filled into the unused mining area. After solidification, an environmentally friendly dust suppressant is added to the industrial water and sprayed as a mist using a high-pressure water spray method. The amount of environmentally friendly dust suppressant added is 8% of the mass of the industrial water, and the unit spraying rate is 0.9 L / m³. 2 3D curing process yields mine filling materials.
[0085] The method for preparing the environmentally friendly dust suppressant in this embodiment includes the following steps:
[0086] S31. Add 2.5 kg of soybean oil and 0.13 kg of glyceryl monolaurate to a reaction vessel, heat to 60°C and stir to form an oil phase. Add 8 kg of esterified starch and 2 kg of carboxymethyl cellulose to 50 kg of deionized water, heat to 90°C and stir at 300 rpm for 1 hour until completely gelatinized. Then add 1.5 kg of the oil phase and shear and stir at 4000 rpm for 2 minutes to prepare an emulsion. Obtain a biodegradable wetting agent by spray drying. The spray drying parameters are: inlet air temperature 170°C, outlet air temperature 80°C, and air volume 700 m³ / h. 3 / h, wind speed is 1.5 m / s.
[0087] S32. Mix 2.5 kg of biodegradable wetting agent, 0.8 kg of polyethylene glycol and 0.2 kg of sodium lignosulfonate to prepare an environmentally friendly dust suppressant.
[0088] Comparative Example 1 differs from Example 1 in that fluorogypsum is replaced with desulfurized gypsum.
[0089] Comparative Example 2 differs from Example 1 in that the composite early strength agent is replaced with triethanolamine.
[0090] Comparative Example 3 differs from Example 1 in that the environmentally friendly dust suppressant is replaced with sodium lignosulfonate.
[0091] Performance testing
[0092] The compressive strength of the mine filling materials prepared in each embodiment and comparative examples 1-2 was tested according to JGJ / T 70-2009 "Standard for Test Methods of Basic Performance of Building Mortar" after curing for 1 day, 3 days, 7 days and 28 days.
[0093] The fluidity and initial setting time of the slurry of the mine filling materials prepared in each example and comparative examples 1-2 were tested according to GB / T 1346-2024 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement".
[0094] The test results are shown in Table 1 below:
[0095] Table 1 Test Results of Mine Backfill Materials
[0096]
[0097] The dried dust was placed in a petri dish, and the dust suppressant solutions prepared in Example 1 and Comparative Example 3 were sprayed at a rate of 2 L / m². 2 The samples were evenly sprayed onto the dust surface, with pure water sprayed as a control. The samples were placed in an indoor ventilated environment to evaporate naturally. The moisture content was tested after 10 hours and 24 hours. The dried dust samples were placed in a wind speed of 7 m / s and the mass loss rate was tested after 30 minutes.
[0098] The test results are shown in Table 2 below:
[0099] Table 2 Dust Suppression Performance
[0100]
[0101] As shown in the table above, the 1-day compressive strength of the mine backfill materials prepared in Examples 1 and 2 is 2.1~2.6 MPa. In Example 3, the mass ratio of cementitious powder to tailings is 1:10, resulting in a smaller bonding contact area and therefore a slower increase in compressive strength. However, the 3-day compressive strength reaches 1.7 MPa, which meets the strength requirements of the mine working face. The gypsum used in Comparative Example 1 is desulfurized gypsum, which causes dehydration during use, resulting in a slurry fluidity of 159 mm, lower than the required fluidity for construction. This indicates that the solid waste fluorogypsum activator for mine backfill prepared in this invention has excellent performance in improving fluidity and strength. The initial setting time of the mine backfill materials prepared in Examples 1~3 is 59~73 min, which decreases with the increase of tailings dosage, but still meets the construction requirements of the mine working face. This indicates that the solid waste fluorogypsum activator for mine backfill prepared in this invention has excellent coagulation-promoting effect and can shorten the setting time.
[0102] The environmentally friendly dust suppressant prepared in Example 1 was used in dust. After 24 hours, the moisture content of the dust was 19.6%, and the mass loss rate of the dust was 0.5% at a wind speed of 7 m / s. This shows that the environmentally friendly dust suppressant prepared in this invention has excellent water retention performance when applied in a mining environment, and also has excellent dust suppression performance under wind conditions of level 4.
[0103] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
[0104] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A solid waste fluorogypsum activator for mine backfilling, characterized in that, It is prepared from the following components in parts by weight: 80-90 parts of fluorogypsum, 10-15 parts of industrial waste residue, 0.1-0.3 parts of composite early strength agent, 2-5 parts of sodium sulfate, and 0.01-0.03 parts of ethylene glycol; The fluorogypsum is a byproduct of hydrofluoric acid production, the industrial waste residue is one or both of blast furnace slag and fly ash, and the mirabilite is a byproduct of soda ash production. The preparation method of the composite early strength agent includes the following steps: S11. Add calcium chloride and aluminum chloride to an ethanol aqueous solution, add sodium carbonate and sodium hydroxide in an ethanol aqueous solution to control the pH, raise the temperature to crystallize the reaction, filter to collect the solid, and dry to obtain calcium aluminum hydrotalcite. S12. Acrylic acid, vinyl polyethylene glycol ether, 2-acrylamido-2-methylpropanesulfonic acid and calcium aluminum hydrotalcite are added to a reaction vessel, deionized water is added and stirred to disperse, sodium sulfite and ammonium persulfate are added dropwise to the reaction vessel, the temperature is raised to react and polymerize, the solid is collected by filtration, washed with ethanol, and dried to obtain coagulation adsorption particles. S13. Mix and grind the coagulation-promoting adsorption particles, triethanolamine and calcium formate to obtain a composite early strength agent; The molar ratio of calcium chloride to aluminum chloride in S11 is 2-3. The ethanol aqueous solution is prepared by mixing ethanol and deionized water at a volume ratio of 1:
1. The molar ratio of sodium carbonate to sodium hydroxide in the ethanol aqueous solution of sodium carbonate and sodium hydroxide is 1:
4. The pH is controlled at 9-10. The crystallization reaction is carried out at 80-90℃ for 10-12 hours and then dried at 60-70℃. In S12, the ratio of acrylic acid, vinyl polyethylene glycol ether, 2-acrylamido-2-methylpropanesulfonic acid, calcium aluminum hydrotalcite, deionized water, sodium sulfite, and ammonium persulfate is (50~55) g : (25~30) g : (5~5.5) g : (3.5~5.5) g : (200~300) mL : (0.8~1.2) g : (1.5~2) g. The mixture is stirred and dispersed at a speed of 70~150 rpm. The sodium sulfite and ammonium persulfate are added dropwise over a period of 1~1.5 h. The mixture is heated to 60~70℃ and reacted for 3~6 h. The mixture is then dried at 60~70℃. In S13, the mass ratio of coagulation-promoting adsorption particles, triethanolamine, and calcium formate is 2~4 : 5~8 : 1.25~2.
2. The preparation method of the solid waste fluorogypsum activator for mine backfilling according to claim 1, characterized in that, Includes the following steps: S1. Fluorogypsum, industrial waste residue and sodium sulfate are added to a grinding mill, ground and sieved to obtain an activator for later use; S2. Add the activator and composite early strength agent to the mixer, add ethylene glycol dropwise, and stir to prepare the solid waste fluorogypsum activator for mine backfilling.
3. The method for preparing the solid waste fluorogypsum activator for mine backfilling according to claim 2, characterized in that, In step S1, the grinding and sieving process achieves a passing rate of over 70% to 200 mesh. In step S2, the mixer is used to stir and mix the mixture for 10-15 minutes at a speed of 70-150 rpm.
4. The application of the solid waste fluorogypsum activator for mine backfilling according to claim 1, characterized in that, Materials used for mine backfilling include the following steps: S21. Solid waste fluorogypsum activator, slag powder and cement used for mine backfilling are added to a mixer and mixed to obtain cementitious powder. Industrial water and tailings are added and stirred to obtain slurry. S22. The grout is injected into the unfilled mining area. After solidification, an environmentally friendly dust suppressant is added to industrial water and sprayed in a mist form using a high-pressure water mist method to cure and obtain the mine filling material.
5. The application of the solid waste fluorogypsum activator for mine backfilling according to claim 4, characterized in that, In S21, the mass ratio of solid waste fluorogypsum activator, slag powder, and cement is 20-30:60-70:10-15, the water-to-solid ratio of the slurry is 0.6-0.7, and the mass ratio of cementitious powder to tailings is 1:4-10. In S22, the amount of environmentally friendly dust suppressant added is 5-8% of the mass of industrial water, and the unit spraying rate is 0.6-0.9 L / m³. 2 1-3 days of maintenance.
6. The application of the solid waste fluorogypsum activator for mine backfilling according to claim 4, characterized in that, The preparation method of the environmentally friendly dust suppressant in S22 includes the following steps: S31. Soybean oil and glyceryl monolaurate are added to a reaction vessel, heated and stirred to form an oil phase. Esterified starch and carboxymethyl cellulose are added to deionized water, heated and stirred until completely gelatinized, and then the oil phase is added. The emulsion is prepared by high-speed shearing and stirring, and a biodegradable wetting agent is obtained by spray drying. S32. A biodegradable wetting agent, polyethylene glycol and sodium lignosulfonate are mixed to prepare an environmentally friendly dust suppressant.
7. The application of the solid waste fluorogypsum activator for mine backfilling according to claim 6, characterized in that, In S31, the mass ratio of soybean oil to glyceryl monolaurate is 100:4-5. The mixture is heated to 50-60℃ and stirred to form an oil phase. The mass ratio of the oil phase, esterified starch, carboxymethyl cellulose, and deionized water is 3-5:10-20:2-5:
100. The mixture is heated to 80-90℃ and stirred at 200-300 rpm for 1-2 hours until completely gelatinized. After adding the oil phase, the mixture is sheared and stirred at 3000-4000 rpm for 1-3 minutes. The spray drying parameters are: inlet air temperature of 160-180℃, outlet air temperature of 60-80℃, and air volume of 500-800 m³ / h. 3 / h, wind speed is 0.8~1.5 m / s; the mass ratio of biodegradable wetting agent, polyethylene glycol and sodium lignosulfonate in S32 is 2~2.5:0.8~1:0.1~0.2.
Citation Information
Patent Citations
An activator for mine backfill materials and its preparation method
CN113060961B
Heat-preservation sound-proof low-density foamed concrete
CN105218146A
Preparation method of concrete early strength agent
CN106365490A